Names in Focus: An Introduction to Finnish Onomastics - Sjöblom, Paula (Studia Fennica Linguistica, 2012)
Names in Focus delves deep into the vast field of Finnish onomastics, covering place names, personal names, animal names, commercial names and names in literature. It provides the history and current trends in this area of research, and also supplements international terminology with the Finnish point of view on the subject. Brimming with examples and clear explanations, the book can be enjoyed by the most studious of researchers as well as the casual reader who has a genuine interest in the study of names.